The Reliability of the Wisconsin Card Sorting Test in Clinical Practice. (January 2021) - Kopp, Bruno; Lange, Florian; Steinke, Alexander
The Wisconsin Card Sorting Test (WCST) represents the gold standard for the neuropsychological assessment of executive function. However, very little is known about its reliability. In the current study, 146 neurological inpatients received the Modified WCST (M-WCST). Four basic measures (number of correct sorts, categories, perseverative errors, set-loss errors) and their composites were evaluated for split-half reliability. The reliability estimates of the number of correct sorts, categories, and perseverative errors fell into the desirable range ( rel ≥ .90). The study therefore disclosed sufficiently reliable M-WCST measures, fostering the application of this eminent psychological test to neuropsychological assessment. Our data also revealed that the M-WCST possesses substantially better psychometric properties than would be expected from previous studies of WCST test-retest reliabilities obtained from non-patient samples. Our study of split-half reliabilities from discretionary construed and from randomly built M-WCST splits exemplifies a novel approach to the psychometric foundation of neuropsychology.